A systematic review of mental health in rural Andean populations in Latin America during the COVID-19 pandemic - Moya-Salazar, Jeel (2023)
“Background: COVID-19 has been causing mental health problems around the world, with rural and indigenous peoples likely to be the most aected. This systematic review synthesizes and critically analyzes the existing literature on mental disorders in the rural Andean population in Latin America. Methods: A systematic review with narrative synthesis was carried out following the PRISMA guidelines. We searched nine databases (PubMed/MEDLINE, Scopus, EMBASE, ScienceDirect, Web of Science, Cochrane, Scielo, LILACS, and Latindex), five public prepublication servers (SocArXiv, medRxiv, bioRxiv, SportRXiv, and Preprints), ALICIA, and Google Scholar for articles that included the analysis of mental health problems using data collected from the rural Andean population in Latin America. These were eligible for inclusion. Articles that included NonLatin American populations (including European or African migrants) and studies conducted prior to the COVID-19 pandemic (since the declaration of national lockdown) were excluded. Results: A total of 23,761 articles were retrieved, 14 of which met the inclusion requirements. Most were cross-sectional (n = 12) and related to anxiety (n = 9), depression (n = 8), and stress (n = 5). The mental health analysis of 5,976 rural dwellers from four countries in Latin America also included gray literature studies (n = 7) that allowed the quantification of mental health problems in adults (n = 7) and adolescents/children (n = 4). Only one study was multinational, and the quality of publications varied. Despite the high frequency of anxiety, depression, and stress symptoms among rural Latin American populations during COVID-19, published research is very limited. This review found preliminary evidence that the frequency of anxiety (45%), depression (27.6%), and stress (33.1%) in the rural population was associated with pandemic restrictions across countries. Measures of other psychiatric problems, such as distress or suicidal ideation, cannot be estimated. Conclusion: Regional-wide studies investigating changes in the frequency of symptoms of mental health problems in the context of the COVID-19 pandemic are warranted to inform culturally adapted prevention strategies. This study is limited to a narrative synthesis and may be subject to publication bia“